Description of the Risk Falls in Elderly People in Cianjur Regency - Haryanto, Ricko Dwi (LPPM STIKes Muhammadiyah Ciamis, 2024)
Various health problems that occur in the elderly result from the deterioration of body cells, resulting in decreased function and endurance. One of the physical health problems that often occurs in the elderly is falls. The consequences of falls experienced by the elderly have psychological, sociological and emotional impacts and will result in physical injury, limited movement and death. This exercise program involves the balance center in the brain and increases the balance response so that it can reduce falls. The aim of this report is to provide an overview of the implementation of comprehensive nursing care for elderly people at risk of falling. Health services in the Cianjur area tend to encourage accelerated changes in the care environment in the health environment, one of which is through counseling services by nurses. Or the implementation of counseling by health workers. Community service activities with the topic Strengthening the Prevention of Fall Risk in the Elderly Age Group in Cianjur Regency is an effort to increase nurses' knowledge in supporting the acceleration of family health independence in Cianjur Regency, especially for the elderly. This research uses quantitative, descriptive methods. Sampling with total sampling. The total research sample was 37 elderly people accompanied by their families. Results: most of the elderly (78.5%) or 25 people were in the risk category for falls around the family. Meanwhile, 21.5% of elderly people are not at risk of falling or as many as 12 elderly people are not at risk of falling.